Chrysophanol Exerts Anti-inflammatory Activity by Targeting Histone Deacetylase 3 Through the High Mobility Group Protein 1-Nuclear Transcription Factor-Kappa B Signaling Pathway in vivo and in vitro - Wen, Quan; Lau, Ngaikeung; Weng, Huandi; Ye, Peng; Du, Shaohui; Li, Chun; Lv, Jianping; Li, Hui (Frontiers in Bioengineering and Biotechnology, 2021)
Chrysophanol (Chr) is the main monomer isolated from Rheum rhabarbarum, The aim of this study was to identify the potential in vitro and in in vivo cytoprotective effects of Chr on LPS-triggered acute lung injury (ALI). We used an ALI-murine model and constructed an inflammatory macrophage in vitro cell model to determine the cellular mechanisms involved in Chr-mediated activity.To observe the vital role of HDAC3 (histone deacetylase 3) in abolishing inflammation action, HDAC3 was downregulated using small interfering RNA (siRNA). Analysis of the expression of nuclear transcription factor kappa B p65 (NF-κB p65) and molecules of its downstream signaling pathway were assessed in vitro and in lung tissue samples using the mouse model. Concentrations of tumor necrosis factor-α (TNF-), interleukin-1β (IL-1β), high mobility group protein 1 (HMGB1), and interleukin-16 (IL-6) in supernatants and in the Bronchoalveolar lavage fluid (BALF) were measured using enzyme linked immunosorbent assay (ELISA). HMGB1 activity was measured by a reporter gene assay, and NF-κB p65 and HMGB1 intracellular localization was determined by immunofluorescence detection on histological lung samples from Chr-treated mice. The protein interactions between HMGB1, HDAC3, and NF-κB p65 were tested by co-immunoprecipitation. Chr treatment relieved LPS-induced lung lesions. Chr also enhanced superoxide dismutase levels in ALI mice. Chr reduced the LPS-induced protein expression of NF-κB and its related pathway molecules in both in vivo and in vitro models. Moreover, Chr downregulated LPS-enhanced HMGB1 expression, acetylation, and nuclear nucleocytoplasmic translocation. However, HDAC3 knockdown substantially reduced Chr-mediated HDAC3/NF-κB expression. Furthermore, Chr enhanced HMGB1/HDAC3/NF-κB p65 complex interaction, while HDAC3 knockdown reduced Chr-mediated HMGB1/HDAC3/NF-κB p65 formation. This study showed that the protective effects induced by Chr were associated with regulation of the HMGB1/NF-κB pathway via HDAC3.